A high temperature resistant and flame retardant hot melt adhesive for power battery packs

By using hot melt adhesives of amorphous polyα olefin resin with high heat resistance and block copolymer PP resin in the power battery pack, combined with flame retardant modified PP wax and Fischer-Tropsch wax modified with magnesium hydroxide and zinc borate, as well as expanded graphite or anatase type titanium dioxide as reinforcement fillers, the problem of reducing the bonding strength of the hot melt adhesive in high temperature environments is solved, and the efficient bonding and flame retardant performance of the hot melt adhesive are achieved.

CN119736036APending Publication Date: 2025-04-01SHENZHEN TONGDE NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411753471.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When the power battery pack is used in a high temperature environment, the bonding strength of the hot melt adhesive is reduced or even failed, resulting in damage to structural integrity and may cause serious consequences such as short circuits and burning.

Method used

Amorphous polyαolefin resin with high heat resistance is used as the matrix resin of the hot melt adhesive, and a small amount of flame retardant and antioxidant is combined with a flame retardant modified PP wax modified by magnesium hydroxide and zinc borate as the wax material, and expanded graphite or anatase titanium dioxide as the reinforcement filler.

Benefits of technology

The softening point of the hot melt adhesive is improved, so that it maintains good bonding strength under the heating state of the power battery pack, improves the flame retardant performance and smoke suppression effect of the hot melt adhesive, reduces the amount of flame retardant added, and ensures the structural integrity and safety of the battery pack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165577360000091
    Figure BDA0005165577360000091
  • Figure BDA0005165577360000101
    Figure BDA0005165577360000101
Patent Text Reader

Abstract

The present invention discloses a high temperature resistant flame retardant hot melt adhesive applied to a power battery pack, and relates to the technical field of hot melt adhesive. A high temperature resistant flame retardant hot melt adhesive comprises 40-55 parts of base resin, 20-35 parts of tackifying resin, 6-10 parts of wax material, 10-16 parts of flame retardant, 4-6 parts of reinforcing filler and 0.8-1 parts of antioxidant, wherein the base resin is composed of amorphous polyalphaolefin resin, or mixed with block copolymer PP resin, the wax material is composed of a mixture of flame retardant modified PP wax and Fischer-Tropsch wax, and the reinforcing filler is composed of at least one of expanded graphite and anatase titanium dioxide. By adopting a specific base resin, in combination with a flame retardant and a wax material and a reinforcing filler having a flame retardant effect, not only the high temperature resistance and bonding performance of the hot melt adhesive can be effectively improved, but also the flame retardant performance of the hot melt adhesive can be improved, which is conducive to improving the adaptability of the hot melt adhesive when applied to a power battery pack, and enables it to be applied to the power battery pack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hot melt adhesives, and in particular to a high temperature resistant and flame retardant hot melt adhesive used in power battery packs. Background Art

[0002] Power battery packs are core components in new energy vehicles, energy storage systems and other fields. Their safety is directly related to the safety of people's lives and property and the sustainable development of the entire society. Hot melt adhesive is an adhesive that changes from solid to liquid when heated. It has the characteristics of fast curing, high strength, water resistance, and temperature resistance. As a common adhesive material, hot melt adhesive is also used in the manufacture and maintenance of power battery packs in certain scenarios. In power battery packs, hot melt adhesive is mainly used for the connection and fixation between battery cells, as well as the bonding between battery packs and vehicle body structures. Through hot melt adhesive technology, the overall structural strength and seismic resistance of the battery pack can be effectively improved, thereby improving the safety and reliability of the battery system.

[0003] First of all, the power battery pack will generate a certain amount of heat during operation, especially in the case of fast charging, high-load operation, etc., the temperature inside the power battery pack will rise sharply, sometimes even reaching a high temperature of about 90-100°C. However, as a thermoplastic material, when the heat inside the power battery pack exceeds the softening point of the hot melt adhesive, the hot melt adhesive will soften or even melt, which may directly lead to a decrease in the bonding strength of the hot melt adhesive, or even failure. Once the bonding fails, the structural integrity inside the power battery pack will be damaged, and may further cause serious consequences such as short circuits and explosions. Secondly, since new energy vehicles may encounter a variety of adverse conditions such as high temperature, high humidity, and bumps during driving, the long-term use environment of the power battery pack is relatively harsh. These adverse external environmental factors may affect the bonding performance of the hot melt adhesive and increase its failure risk.

[0004] Therefore, in the preparation and maintenance of power battery packs, the impact of these adverse factors on hot melt adhesives should be fully considered, so as to improve the performance of the hot melt adhesive itself and make it more suitable for use in power battery packs, which is of great significance to ensure the safe and stable operation of the battery. Summary of the invention

[0005] In order to further improve the heat resistance of the hot melt adhesive, enable it to maintain good adhesion performance in harsh environments such as high temperature and high humidity, and improve the adaptability of the hot melt adhesive in power battery packs, the present application provides a high temperature resistant and flame retardant hot melt adhesive for use in power battery packs.

[0006] In the first aspect, the present application provides a high temperature resistant flame retardant hot melt adhesive adopts the following technical solution: A high temperature resistant flame retardant hot melt adhesive, comprising the following raw materials in parts by weight: Base resin: 40-55 parts; Tackifying resin: 20-35 parts; Wax material: 6-10 parts; Flame retardant: 10-16 parts; Reinforcing filler: 4-6 parts; 0.8-1 part of antioxidant; The matrix resin comprises an amorphous poly-alpha olefin resin, or a mixture of an amorphous poly-alpha olefin resin and a block copolymer PP resin; the wax material comprises a flame retardant modified PP wax and a Fischer-Tropsch wax mixed in a weight ratio of 1:(0.5-1); and the reinforcing filler comprises at least one of expanded graphite and anatase titanium dioxide.

[0007] By adopting the above technical solution, using amorphous poly-α-olefin resin with high heat resistance as the base resin of hot melt adhesive, the softening point of hot melt adhesive can be increased to above 110°C, so as to meet the performance requirements of hot melt adhesive to maintain good bonding strength under the heating state of power battery pack, which is conducive to improving the adaptability of hot melt adhesive when applied to power battery pack. Secondly, using flame-retardant modified PP wax modified by magnesium hydroxide and zinc borate and Fischer-Tropsch wax as wax material, using expanded graphite or anatase titanium dioxide with certain flame retardant properties as reinforcing filler, and adding a small amount of flame retardant, it can not only effectively improve the flame retardant properties of hot melt adhesive, and make the hot melt adhesive have excellent smoke suppression effect, but also reduce the amount of flame retardant added, so that the hot melt adhesive has good bonding properties. Therefore, when the battery has thermal runaway, the hot melt adhesive can quickly form a solid flame retardant barrier to prevent the spread of fire, and maintain a certain degree of bonding, temporarily maintaining the structural integrity of the power battery pack, and effectively protecting the safety of the battery pack and the surrounding environment.

[0008] Optionally, the preparation of the flame retardant modified PP wax comprises the following steps: A1. Mix magnesium hydroxide and zinc borate in a weight ratio of 1: (0.05-0.2) to obtain a mixed powder, then add it into deionized water at a temperature not higher than 10° C. and stir it for 15-20 minutes to obtain a suspension slurry; add a coupling agent to the suspension slurry, wherein the amount of the coupling agent added is 2%-4% of the weight of the mixed powder, then keep the temperature and stir it for 2-3 hours, filter it under reduced pressure, fully dry it, and crush it to obtain a modified powder; A2. Take the flame retardant modified powder obtained in step A1 and PP wax in a weight ratio of 1: (2-2.5), fully mix them and heat and dry them for 10-20 minutes, then granulate them by melt extrusion, and obtain the flame retardant modified PP wax after the granules are dried.

[0009] By adopting the above technical scheme, PP wax is flame-retardantly modified by using magnesium hydroxide and zinc borate, and PP wax can fully cover and evenly disperse magnesium hydroxide and zinc borate in the hot melt adhesive. When the hot melt adhesive burns, magnesium hydroxide can absorb heat and decompose, and release part of water vapor while forming a magnesium oxide protective layer, which is beneficial to isolating oxygen and most of the heat, and is also beneficial to diluting the combustible gas and reducing the oxygen concentration in the combustion area, and to a certain extent inhibiting the generation of smoke caused by the burning of the hot melt adhesive; and zinc borate can also react with magnesium oxide by absorbing heat and generate a new crystalline phase, and generate a stable porous residue similar to glass and ceramics. Through the synergistic cooperation of magnesium hydroxide and zinc borate, it can further insulate and prevent air from diffusing into the material, and hinder the hot melt adhesive from continuing to burn, and prevent the hot melt adhesive based on polyolefin from dripping when burning, which is beneficial to improving the flame retardant properties of the hot melt adhesive.

[0010] Optionally, the coupling agent in step A1 includes a titanate coupling agent and a silane coupling agent mixed and compounded, and the titanate coupling agent and the silane coupling agent are mixed in a weight ratio of 1: (1-1.4); The titanate coupling agent includes at least one of isopropyl tri(isostearoyl) titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, and isopropyl di(methacryloyl) isostearyl titanate, and the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane and dodecyltrimethoxysilane.

[0011] By adopting the above technical scheme, a certain synergistic coupling effect can be produced between the titanate coupling agent and the silane coupling agent, and the dispersibility of magnesium hydroxide and zinc borate in PP wax can be fully improved, which is beneficial to reduce the agglomeration of the mixed powder in the PP wax and improve the modification effect of the flame retardant modified PP wax.

[0012] Optionally, the matrix resin is a mixture of the amorphous poly-alpha olefin resin and the block copolymer PP resin in a weight ratio of 1:(0.2-0.4).

[0013] By adopting the above technical solution, since the block copolymer PP resin has a high crystallinity and melting point, the amorphous poly-α-olefin resin and the block copolymer PP resin are mixed and compounded as the base resin of the hot melt adhesive, which is beneficial to improve the softening point of the hot melt adhesive from the base and improve the overall high temperature resistance of the hot melt adhesive. Secondly, since there are relatively long ethylene blocks in the molecular chain of the block copolymer PP resin, it can play a role of physical crosslinking with the amorphous poly-α-olefin resin through the crystallization of the polyethylene segment. At the same time, the block copolymer PP resin molecular chain has the characteristics of high static shear viscosity and good melt strength, which is beneficial to improve the cohesive strength of the hot melt adhesive and further improve the bonding performance of the hot melt adhesive.

[0014] Optionally, the tackifying resin includes C5 hydrogenated petroleum resin and hydrogenated DCPD petroleum resin, and the C5 hydrogenated petroleum resin and the hydrogenated DCPD petroleum resin are mixed and compounded in a weight ratio of 1:(1.5-4).

[0015] By adopting the above technical solution, it is beneficial to improve the bonding strength of the hot melt adhesive while maintaining a high softening point of the hot melt adhesive. In addition, since hydrogenated DCPD petroleum resin has excellent cohesive strength, thermal stability and oxidation resistance, as the proportion of hydrogenated DCPD petroleum resin increases within this range, the bonding performance and high temperature resistance of the hot melt adhesive can be further improved, and the aging resistance of the hot melt adhesive can also be improved.

[0016] Optionally, the reinforcing filler is a mixture of expanded graphite and titanium dioxide in a weight ratio of (1-7):1.

[0017] By adopting the above technical scheme, expanded graphite and titanium dioxide can not only reinforce and harden the hot melt adhesive with a polyolefin matrix resin, making it easier to process and shape, but also improve the flame retardant properties of the hot melt adhesive to a certain extent through endothermic expansion or crystal transformation. Secondly, compared with adding only one reinforcing filler alone, the hot melt adhesive mixed with expanded graphite and titanium dioxide in a weight ratio of (1-7):1 has not only a higher softening point and high temperature resistance, but also better bonding performance, cohesive strength and flame retardant performance, and better comprehensive performance.

[0018] Optionally, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168, and the mixing weight ratio of the antioxidant 1010 to the antioxidant 168 is 1:(2.2-3).

[0019] By adopting the above technical solution, when the antioxidant 1010 and the antioxidant 168 can produce a certain synergistic effect, it is beneficial to improve the antioxidant properties of the hot melt adhesive and can effectively prevent the hot melt adhesive from turning yellow or reducing its viscosity due to oxidation after being placed for a long time.

[0020] In the second aspect, the present application provides a method for preparing a high temperature resistant flame retardant hot melt adhesive using the following technical solution: A method for preparing a high temperature resistant flame retardant hot melt adhesive, comprising the following steps: S1. First, 10% of the base resin, wax, flame retardant and antioxidant are fully mixed at a mixing temperature of 165-180° C., and then the remaining base resin and reinforcing filler are added, and the mixture is fully stirred to obtain a first mixture; the temperature is lowered to 140-155° C., a tackifying resin is added, and stirring is continued for 20-30 minutes to obtain a second mixture; S2. The second mixture is subjected to vacuum exhaust treatment, and then melt-extruded, and quickly pulled into a circulating cooling water tank with a cooling solution temperature not higher than 5° C. for cooling, and then crushed and granulated to a fixed length, and dried to obtain a high-temperature resistant and flame-retardant hot melt adhesive.

[0021] By adopting the above technical solution, the mixing temperature is lowered when mixing the tackifying resin, which is beneficial to reducing the impact of high temperature on the tackifying resin, can effectively prevent the tackifying resin from yellowing, and is beneficial to improving the appearance performance of the hot melt adhesive. After the hot melt adhesive is extruded, it is quickly cooled. The low-temperature cooling solution can not only quickly shape the hot melt adhesive, but also prevent the hot melt adhesive from crystallizing, thereby helping to reduce the impact on the transparency and other properties of the product. In addition, the preparation method is simple in process, which is conducive to subsequent mass production.

[0022] Optionally, in step S2, the cooling solution includes 3%-5% anti-adhesive liquid and the remainder is deionized water.

[0023] By adopting the above technical scheme, a certain concentration of anti-sticking liquid is added to the cooling solution, so that the surface of the hot melt adhesive can be anti-sticked while it is cooling and shaping, further simplifying the process flow. It is not only beneficial to prevent the knife from sticking when the hot melt adhesive is crushed and granulated to a fixed length, but also beneficial to the subsequent transportation and storage of the hot melt adhesive.

[0024] In the third aspect, the application method of a high temperature resistant flame retardant hot melt adhesive provided in the present application adopts the following technical solution: an application of a high temperature resistant flame retardant hot melt adhesive is applied to the structural bonding of a power battery pack.

[0025] In summary, the technical solution of this application includes at least one of the following beneficial effects: 1. By using amorphous poly-α-olefin resin with high heat resistance as the base resin of the hot melt adhesive, the softening point of the hot melt adhesive can be increased to above 110°C, thereby meeting the performance requirements of the hot melt adhesive to maintain good bonding strength when the power battery pack is heated, which is beneficial to improving the adaptability of the hot melt adhesive when applied to the power battery pack.

[0026] 2. By adding a certain amount of block copolymer PP resin into the matrix resin, it is helpful to increase the softening point of the hot melt adhesive from the matrix and improve the overall high temperature resistance and bonding performance of the hot melt adhesive.

[0027] 3. By using a flame-retardant modified PP wax modified by magnesium hydroxide and zinc borate and a compound with Fischer-Tropsch wax as the wax material, and using expanded graphite or anatase titanium dioxide with certain flame retardant properties as reinforcing fillers, and adding a small amount of flame retardant, the flame retardant properties of the hot melt adhesive can be effectively improved, and it can have an excellent smoke suppression effect. Therefore, when the battery has thermal runaway, the hot melt adhesive can quickly form a solid flame retardant barrier to prevent the spread of fire and effectively protect the safety of the battery pack and the surrounding environment. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0029] Preparation Example [Preparation Example 1] A flame retardant modified PP wax comprises the following preparation steps: A1. Take 4 kg of magnesium hydroxide and 0.2 kg of zinc borate and mix them thoroughly to obtain a mixed powder, then add them into deionized water at 10° C. and stir for 15 min to obtain a suspension slurry; add 126 g of a coupling agent to the suspension slurry, wherein the coupling agent is a titanate coupling agent and a silane coupling agent mixed and compounded in a weight ratio of 1:1, specifically including 63 g of isopropyl tri(isostearyl) titanate and 63 g of dodecyltrimethoxysilane, then keep the temperature and stir for 3 h, fully dry the filter cake after vacuum filtration, and fully crush the filter cake using a high-speed disperser to obtain a modified powder; A2. Take 4 kg of the modified powder obtained in step A1 and mix it with 8 kg of PP wax, heat it to 70°C and dry it with hot air for 20 min, then granulate it by melt extrusion. After the granules are dried, a flame retardant modified PP wax is obtained.

[0030] [Preparation Example 2] A flame retardant modified PP wax comprises the following preparation steps: A1. Take 4 kg of magnesium hydroxide and 0.8 kg of zinc borate and mix them thoroughly to obtain a mixed powder, then add them into deionized water at 10°C and stir for 20 minutes to obtain a suspension slurry; add 192 g of a coupling agent to the suspension slurry, wherein the coupling agent is a titanate coupling agent and a silane coupling agent mixed and compounded according to a weight ratio of 1:1.4, specifically including 60 g of isopropyl tri(dodecylbenzenesulfonyl) titanate, 20 g of isopropyl tri(dodecylbenzenesulfonyl) titanate and 112 g of γ-methacryloxypropyltrimethoxysilane, then keep the temperature and stir for 2 hours, fully dry the filter cake after vacuum filtration, and fully crush the filter cake using a high-speed disperser to obtain a modified powder; A2. Take 4 kg of the modified powder obtained in step A1 and mix it with 10 kg of PP wax, heat it to 80°C and dry it with hot air for 10 minutes, then granulate it by melt extrusion. After the granules are dried, a flame retardant modified PP wax is obtained.

[0031] [Preparation Example 3] A flame retardant modified PP wax, which differs from [Preparation Example 1] in that the ratio of magnesium hydroxide to zinc borate in the mixed powder in step A1 is different. Specifically, the mixing weight ratio of magnesium hydroxide to zinc borate is 1:0.15, that is, in this preparation example, 4 kg of magnesium hydroxide and 0.6 kg of zinc borate are fully mixed to obtain a mixed powder.

[0032] [Preparation Example 4] A flame retardant modified PP wax, which differs from [Preparation Example 1] in that the ratio of magnesium hydroxide to zinc borate in the mixed powder in step A1 is different. Specifically, the mixing weight ratio of magnesium hydroxide to zinc borate is 1:0.2, that is, in this preparation example, 4 kg of magnesium hydroxide and 0.8 kg of zinc borate are fully mixed to obtain a mixed powder. Example

[0033] [Example 1] A high temperature resistant flame retardant hot melt adhesive comprises the following raw materials: 55 kg of base resin, 20 kg of tackifying resin, 6 kg of wax material, 15 kg of flame retardant, 4 kg of reinforcing filler and 1 kg of antioxidant.

[0034] The matrix resin is an amorphous poly-alpha-olefin resin, specifically Evonik APAO 703, which has a softening point of 126°C.

[0035] The tackifying resin is a mixture of C5 hydrogenated petroleum resin and hydrogenated DCPD resin in a weight ratio of 1:1.5, namely, 8 kg of hydrogenated petroleum resin and 12 kg of hydrogenated DCPD resin.

[0036] The wax material is a mixture of flame retardant modified PP wax and Fischer-Tropsch wax in a weight ratio of 1:0.5, namely, 4 kg of flame retardant modified PP wax and 2 kg of Fischer-Tropsch wax. Specifically, the flame retardant modified PP wax is a flame retardant modified PP wax prepared in [Preparation Example 1].

[0037] The flame retardant is Doher-8303. The reinforcing filler is expanded graphite with a specific mesh size of 325 meshes.

[0038] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3, namely, 0.25 kg of antioxidant 1010 and 0.75 kg of antioxidant 168.

[0039] A method for preparing a high temperature resistant flame retardant hot melt adhesive comprises the following steps: S1. First, 10% of the base resin, wax, flame retardant and antioxidant are fully mixed at a mixing temperature of 165° C., and then the remaining base resin and reinforcing filler are added, and the mixture is fully stirred to obtain a first mixture; the temperature is lowered to 140° C., a tackifying resin is added, and stirring is continued for 30 minutes to obtain a second mixture; S2, vacuum exhaust treatment is performed on the second mixture, and then melt extrusion is performed, and the mixture is quickly pulled into a circulating cooling water tank with a cooling solution temperature of 5°C for cooling, wherein the cooling solution includes 5% anti-adhesive liquid and 95% deionized water, and then the mixture is crushed and granulated to a fixed length, and a high temperature resistant flame retardant hot melt adhesive is obtained after drying. Specifically, the anti-adhesive liquid is selected from SH-3011 hot melt adhesive anti-adhesive agent.

[0040] A high temperature resistant and flame retardant hot melt adhesive is used for structural bonding of power battery packs.

[0041] [Example 2] A high temperature resistant and flame retardant hot melt adhesive comprises the following raw materials: 40 kg of base resin, 35 kg of tackifying resin, 10 kg of wax material, 10 kg of flame retardant, 6 kg of reinforcing filler and 0.8 kg of antioxidant.

[0042] The base resin is a mixture of amorphous polyalphaolefin resin and block copolymer PP resin in a weight ratio of 1:0.2, namely, 33.3 kg amorphous polyalphaolefin resin and 6.7 kg block copolymer PP resin. Specifically, the amorphous polyalphaolefin resin is Evonik APAO 703, and the block copolymer PP resin is Korean SK B350F.

[0043] The tackifying resin is a mixture of C5 hydrogenated petroleum resin and hydrogenated DCPD resin in a weight ratio of 1:4, namely, 7 kg of hydrogenated petroleum resin and 28 kg of hydrogenated DCPD resin.

[0044] The wax material is a mixture of flame retardant modified PP wax and Fischer-Tropsch wax in a weight ratio of 1:1, namely, 5 kg of flame retardant modified PP wax and 5 kg of Fischer-Tropsch wax. Specifically, the flame retardant modified PP wax is a flame retardant modified PP wax prepared in [Preparation Example 2].

[0045] The flame retardant is Doher-8303. The reinforcing filler is anatase titanium dioxide, specifically Shanghai Yuejiang's titanium dioxide A101.

[0046] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:2.2, namely, 0.25 kg of antioxidant 1010 and 0.55 kg of antioxidant 168.

[0047] A method for preparing a high temperature resistant flame retardant hot melt adhesive comprises the following steps: S1. First, 10% of the base resin, wax, flame retardant and antioxidant are fully mixed at a mixing temperature of 180°C, and then the remaining base resin and reinforcing filler are added, and the mixture is fully stirred to obtain a first mixture; the temperature is lowered to 155°C, a tackifying resin is added, and stirring is continued for 20 minutes to obtain a second mixture; S2, vacuum exhaust treatment is performed on the second mixture, and then melt extrusion is performed, and the mixture is quickly pulled into a circulating cooling water tank with a cooling solution temperature of 5°C for cooling, wherein the cooling solution includes 3% anti-adhesive liquid and 97% deionized water, and then the mixture is crushed and granulated to a fixed length, and dried to obtain a high temperature resistant flame retardant hot melt adhesive. Specifically, the anti-adhesive liquid is selected from SH-3011 hot melt adhesive anti-adhesive agent.

[0048] A high temperature resistant and flame retardant hot melt adhesive is used for structural bonding of power battery packs.

[0049] [Example 3] A high temperature resistant and flame retardant hot melt adhesive, which differs from [Example 1] in that the base resin is different.

[0050] In this embodiment, the base resin is replaced by equal amounts of amorphous poly-alpha olefin resin and block copolymer PP resin mixed in a weight ratio of 1:0.2, namely, including 45.83 kg of amorphous poly-alpha olefin resin and 9.17 kg of block copolymer PP resin.

[0051] A method for preparing a high temperature resistant flame retardant hot melt adhesive, which differs from [Example 1] in that the mixing process temperature when mixing the first mixture and the second mixture in step S1 is different.

[0052] In this embodiment, 10% of the base resin, wax, flame retardant and antioxidant are first fully mixed at a mixing temperature of 180°C, and then the remaining base resin and reinforcing filler are added, and the mixture is fully stirred and mixed to obtain a first mixture; the temperature is lowered to 155°C, a tackifying resin is added, and stirring is continued for 20 minutes to obtain a second mixture.

[0053] [Example 4] A high temperature resistant and flame retardant hot melt adhesive, which differs from [Example 3] in that the base resin is different.

[0054] In this embodiment, the base resin is replaced by equal amounts of amorphous poly-alpha olefin resin and block copolymer PP resin mixed in a weight ratio of 1:0.4, namely, including 39.28 kg of amorphous poly-alpha olefin resin and 15.71 kg of block copolymer PP resin.

[0055] [Example 5] A high temperature resistant and flame retardant hot melt adhesive, which differs from Example 4 in that the wax material is different.

[0056] In this embodiment, the flame retardant modified PP wax in the wax material is specifically selected from a flame retardant modified PP wax prepared in [Preparation Example 3].

[0057] [Example 6] A high temperature resistant and flame retardant hot melt adhesive, which differs from Example 4 in that the wax material is different.

[0058] In this embodiment, the flame retardant modified PP wax in the wax material is specifically selected from a flame retardant modified PP wax prepared in [Preparation Example 4].

[0059] [Example 7] A high temperature resistant and flame retardant hot melt adhesive, which differs from Example 5 in that the wax material is different.

[0060] In this embodiment, the flame retardant modified PP wax and the Fischer-Tropsch wax are mixed and compounded in a weight ratio of 1:1, namely, including 3 kg of flame retardant modified PP wax and 3 kg of Fischer-Tropsch wax.

[0061] [Example 8] A high temperature resistant and flame retardant hot melt adhesive, which differs from [Example 7] in that the reinforcing filler is different.

[0062] In this embodiment, the reinforcing filler is replaced by anatase titanium dioxide in equal amounts, and specifically titanium dioxide A101 produced by Shanghai Yuejiang is selected.

[0063] [Example 9] A high temperature resistant and flame retardant hot melt adhesive, which differs from [Example 8] in that the reinforcing filler is different.

[0064] In this embodiment, the reinforcing filler is replaced by an equal amount of expanded graphite and anatase titanium dioxide mixed in a weight ratio of 1:1, that is, including 2 kg of expanded graphite and 2 kg of anatase titanium dioxide.

[0065] [Example 10] A high temperature resistant and flame retardant hot melt adhesive, which differs from [Example 8] in that the reinforcing filler is different.

[0066] In this embodiment, the reinforcing filler is replaced by an equal amount of expanded graphite and anatase titanium dioxide mixed in a weight ratio of 3:1, that is, including 3 kg of expanded graphite and 1 kg of anatase titanium dioxide.

[0067] Comparative Example [Comparative Example 1] A hot melt adhesive, which differs from [Example 1] in that the wax material is a mixture of ordinary PP wax and Fischer-Tropsch wax, and the reinforcing filler is replaced by an equal amount of carbon black.

[0068] [Comparative Example 2] A hot melt adhesive, which differs from [Example 1] in that no Fischer-Tropsch wax is added to the wax material, and the Fischer-Tropsch wax is replaced in equal amounts with a flame retardant modified PP wax prepared in [Preparation Example 1], that is, in this comparative example, the amount of flame retardant modified PP wax added is 6 kg.

[0069] [Comparative Example 3] A hot melt adhesive, which differs from [Example 1] in that no reinforcing filler is added.

[0070] Performance test data 1. Softening point test (melting temperature): refer to "GB / T 15332-1994 Hot Melt Adhesive Softening Point Ring and Ball Method" for testing, and record the lowest temperature (℃) when the softening state is reached. Among them, silicone oil is used as the heating medium.

[0071] 2. High temperature bonding strength: Refer to GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material) for testing, and record the tensile shear strength (MPa) and bonding interface failure type of each embodiment and comparative example. The bonding medium is aluminum plate, and the test temperature is set at 80°C.

[0072] 3. Flame retardant performance test: The hot melt adhesive prepared in each embodiment and comparative example was first melted and remolded into a 127 mm long and 13 mm wide hot melt adhesive strip, and then tested with reference to the 94V-0, 94V-1, and 94V-2 vertical burning tests in the "UL94 Flame Retardant Grade Standard", and the flame retardant grade of each embodiment and comparative example was recorded.

[0073] 4. Smoke density rating (SDR): Refer to GB / T 8627-2007 Test method for smoke density of burning or decomposition of building materials, and record the smoke density rating of each embodiment and comparative example. The test sample should refer to the standard size of the test sample in Chapter 5 to melt the hot melt adhesive prepared in each embodiment and comparative example and reshape it.

[0074] Table 1 Partial performance test data of hot melt adhesive Combining Example 1 with Comparative Example 1 and the data in Table 1, it can be seen that by using amorphous poly-alpha-olefin resin with high heat resistance as the base resin of the hot melt adhesive, the softening point of the hot melt adhesive can be increased to greater than 110°C, thereby meeting the performance requirement that the hot melt adhesive can maintain good bonding strength when the power battery pack is heated. Secondly, by comparing the flame retardant data of Example 1 and Comparative Example 1, it can be seen that the flame retardant modified PP wax modified by magnesium hydroxide and zinc borate and the Fischer-Tropsch wax are compounded in the wax material, and the expanded graphite with flame retardant properties can effectively improve the flame retardant properties and smoke suppression effect of the hot melt adhesive.

[0075] Combining Example 1 with Example 3-4 and the data in Table 1, it can be seen that when a certain amount of block copolymer PP resin is added to the base resin, the softening point of the hot melt adhesive can be increased, and at the same time, the bonding performance of the hot melt adhesive can be improved, and as the proportion of the block copolymer PP resin increases, its effect can be further improved. This may be because the block copolymer PP resin itself can maintain the crystallinity and melting point of homopolypropylene to a certain extent, so it has a higher softening point, which is beneficial to improve the softening point of the hot melt adhesive and improve the high temperature resistance. In addition, there are longer ethylene blocks in the block copolymer PP resin molecular chain, and it can play a role in physical crosslinking with the amorphous poly-alpha olefin resin through the crystallization of the polyethylene segment. At the same time, the block copolymer PP resin molecular chain has the characteristics of high static shear viscosity and good melt strength, which is beneficial to further improve the bonding performance of the hot melt adhesive.

[0076] Combining Examples 4-6 and the data in Table 1, it can be seen that when the mixing ratio of magnesium hydroxide and zinc borate in the mixed powder modified with flame-retardant modified PP wax is in the range of 1:(0.05-0.2), as the proportion of zinc borate increases, the smoke suppression effect of the hot melt adhesive can be improved accordingly. This may be because the flame-retardant modified PP wax actually uses PP wax as a carrier and magnesium hydroxide and zinc borate as flame-retardant fillers to modify the hot melt adhesive. Since PP wax can be evenly dispersed in the hot melt adhesive system with polyolefin as the base resin, magnesium hydroxide and zinc borate can be fully dispersed and mixed in the hot melt adhesive through the PP wax. When the hot melt adhesive burns, magnesium hydroxide can absorb heat and decompose, and release part of the water vapor while forming a magnesium oxide protective layer, which is beneficial for isolating oxygen and most of the heat, and is also beneficial for diluting the combustible gas and reducing the oxygen concentration in the combustion area, inhibiting the generation of smoke to a certain extent; and zinc borate can absorb heat and react with magnesium oxide to generate a new crystalline phase after being heated at high temperature, and generate a stable porous residue similar to glass and ceramics, which is beneficial for further insulation and preventing air from diffusing into the material. It has a synergistic effect, further reduces the generation of smoke, and improves the flame retardant and smoke suppression effect of the hot melt adhesive.

[0077] Secondly, from the data of Examples 4-6, it can be seen that when the mixing ratio of magnesium hydroxide and zinc borate is in the range of 1:(0.15-0.2), as the proportion of zinc borate increases, the smoke suppression effect of the hot melt adhesive is not greatly improved. However, the cost of zinc borate is relatively high. Therefore, the mixed powder of magnesium hydroxide and zinc borate in a mixing ratio of 1:0.15 is used to modify the PP wax, which not only greatly improves the smoke suppression effect of the hot melt adhesive, but also helps to save raw material costs.

[0078] Combining Example 1 with Comparative Example 2, Example 5 with Example 7 and the data in Table 1, it can be seen that when a certain amount of Fischer-Tropsch wax is added to the wax material, the hot melt adhesive can not only have a higher softening point, but also the high-temperature bonding strength is slightly improved, and the heat resistance is improved. This may be because Fischer-Tropsch wax has the characteristics of high melting point and high hardness. As the proportion of Fischer-Tropsch wax in the wax material increases, the heat resistance of the hot melt adhesive can be effectively improved. Moreover, as the proportion of Fischer-Tropsch wax in the wax material increases, the softening point of the hot melt adhesive will also increase, but the high-temperature bonding strength will decrease. This may be because the melt viscosity of Fischer-Tropsch wax is low, and adding too much will affect the bonding performance of the hot melt adhesive.

[0079] Combining Example 1 with Comparative Example 3, Examples 7-10 and the data in Table 1, it can be seen that adding flame retardant fillers such as expanded graphite or anatase titanium dioxide as reinforcing fillers in the hot melt adhesive can make the hot melt adhesive have a higher softening point and better bonding strength to a certain extent, and can also improve the flame retardant properties of the hot melt adhesive. Secondly, when anatase titanium dioxide is used to replace expanded graphite in equal amounts, the softening point and flame retardant grade of the hot melt adhesive decrease slightly, but its high-temperature bonding strength and cohesive strength are improved. When the reinforcing filler is selected from expanded graphite and anatase titanium dioxide and mixed in a ratio of (1-7): 1, compared with adding only one reinforcing filler alone, the hot melt adhesive has both a higher softening point and high temperature resistance, and has better bonding performance, cohesive strength and flame retardant properties, and better comprehensive performance.

[0080] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high temperature resistant flame retardant hot melt adhesive, characterized in that: It includes the following raw materials in parts by weight: Base resin: 40-55 parts; Tackifying resin: 20-35 parts; Wax material: 6-10 parts; Flame retardant: 10-16 parts; Reinforcing filler: 4-6 parts; 0.8-1 part of antioxidant; The matrix resin comprises an amorphous poly-alpha olefin resin, or a mixture of an amorphous poly-alpha olefin resin and a block copolymer PP resin; the wax material comprises a mixture of flame-retardant modified PP wax and Fischer-Tropsch wax in a weight ratio of 1: (0.5-1); and the reinforcing filler comprises at least one of expanded graphite and anatase titanium dioxide.

2. The high temperature resistant flame retardant hot melt adhesive according to claim 1, characterized in that: The preparation of the flame retardant modified PP wax comprises the following steps: A1. Mix magnesium hydroxide and zinc borate in a weight ratio of 1: (0.05-0.2) to obtain a mixed powder, then add it into deionized water at a temperature not higher than 10°C and stir it for 15-20 minutes to obtain a suspension slurry; add a coupling agent to the suspension slurry, wherein the amount of the coupling agent added is 2%-4% of the weight of the mixed powder, then keep the temperature and stir it for 2-3 hours, filter it under reduced pressure, fully dry it, and crush it to obtain a modified powder; A2. Take the flame retardant modified powder obtained in step A1 and PP wax in a weight ratio of 1: (2-2.5), fully mix them and heat and dry them for 10-20 minutes, then granulate them by melt extrusion, and obtain the flame retardant modified PP wax after the granules are dried.

3. The high temperature resistant flame retardant hot melt adhesive according to claim 2, characterized in that: The coupling agent in step A1 includes a titanate coupling agent and a silane coupling agent mixed and compounded, and the titanate coupling agent and the silane coupling agent are mixed in a weight ratio of 1: (1-1.4); The titanate coupling agent includes at least one of isopropyl tri(isostearoyl) titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, and isopropyl di(methacryloyl) isostearyl titanate, and the silane coupling agent includes at least one of γ-methacryloxypropyl trimethoxy silane and dodecyl trimethoxy silane.

4. The high temperature resistant flame retardant hot melt adhesive according to claim 1, characterized in that: The matrix resin is a mixture of the amorphous poly-alpha-olefin resin and the block copolymer PP resin in a weight ratio of 1:(0.2-0.4).

5. The high temperature resistant flame retardant hot melt adhesive according to claim 1, characterized in that: The tackifying resin comprises C5 hydrogenated petroleum resin and hydrogenated DCPD petroleum resin, and the C5 hydrogenated petroleum resin and the hydrogenated DCPD petroleum resin are mixed and compounded in a weight ratio of 1:(1.5-4).

6. The high temperature resistant flame retardant hot melt adhesive according to claim 1, characterized in that: The reinforcing filler is a mixture of expanded graphite and titanium dioxide in a weight ratio of (1-7):

1.

7. The high temperature resistant flame retardant hot melt adhesive according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, and the mixing weight ratio of the antioxidant 1010 to the antioxidant 168 is 1:(2.2-3).

8. A method for preparing a high temperature resistant flame retardant hot melt adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. First, 10% of the base resin, wax, flame retardant and antioxidant are fully mixed at a mixing temperature of 165-180° C., and then the remaining base resin and reinforcing filler are added, and the mixture is fully stirred to obtain a first mixture; the temperature is lowered to 140-155° C., a tackifying resin is added, and stirring is continued for 20-30 minutes to obtain a second mixture; S2. The second mixture is subjected to vacuum exhaust treatment, and then melt-extruded, and quickly pulled into a circulating cooling water tank with a cooling solution temperature not higher than 5° C. for cooling, and then crushed and granulated to a fixed length, and dried to obtain a high-temperature resistant and flame-retardant hot melt adhesive.

9. The method for preparing a high temperature resistant flame retardant hot melt adhesive according to claim 8, characterized in that: In step S2, the cooling solution includes 3%-5% anti-adhesive liquid and the balance is deionized water.

10. Use of the high temperature resistant flame retardant hot melt adhesive according to any one of claims 1 to 7 in a power battery pack.